Adult health promotion record (AHPR) - a tool for prevention of lifestyle related epidemic chronic diseases - Katulanda, P.; Wickramasinghe, K.; Ranasinghe, D.C.; Matthews, D.R.; Sheriff, M.H.R. (My University, 2008)
Background: The disease epidemiology in Sri Lanka has changed and the non-communicable diseases (NCDs) have become main causes of mortality and morbidity. Most epidemic chronic diseases are related to lifestyle and have common risk factors. Despite studies showing that they can be prevented by lifestyle modification, such knowledge has not translated into community level prevention. Objectives: To develop a simple and low cost tool that can be used by community health workers and the individuals themselves for prevention of lifestyle related NCDs similar to the highly successful Child Health Development Record. Design, setting and methods: We identified cardiovascular disease, type 2 diabetes, obstructive pulmonary disease, alcoholic cirrhosis, tobacco and lifestyle related malignancies as important causes of mortality, morbidity and economic burden in Sri Lanka and the world with potential for prevention by lifestyle modification. Next, based on current evidence we identified obesity, physical inactivity, tobacco smoking, hypertension, alcohol abuse, hyperlipidaemia and elevated plasma glucose as factors that can be changed through lifestyle modification. The AHPR was developed to indicate graded risk for body weight, body mass index, waist circumference, blood pressure, fasting plasma glucose, HDL-C, triglycerides, LDL-C, physical exercise, smoking and alcohol consumption coded in green, yellow, amber and red colours based on currently available ethnic and gender specific data. The AHPR is for progressive follow up and include vital messages and recommendations for health promotion and disease prevention. Conclusions: This simple, low cost tool for NCD prevention may be used in research and public health interventions to assess its efficacy and cost effectiveness.
Sri Lanka Medical Association - 121st Annual Scientific Sessions: 2008; 53p.